Quantifying the Energy Losses in CsPbI2Br Perovskite Solar Cells with an Open-Circuit Voltage of up to 1.45 v - Tian, Jingjing; Zhang, Kaicheng; Xie, Zhiqiang; Peng, Zijian; Zhang, Jiyun; Osvet, Andres; Lüer, Larry; Kirchartz, Thomas; Rau, Uwe; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2022)
CsPbI2Br perovskite solar cells (PSCs) have attracted much interest because of their thermodynamic stability, relatively stable cubic perovskite phase, and their potential as a top cell for tandem applications. However, the open-circuit voltage (VOC) reported to date is in most cases well below the detailed balance (DB) limit for single-junction PSCs. Here, we demonstrate that adding lead acetate to the CsPbI2Br precursor allows us to substantially reduce losses due to nonradiative recombination. Corresponding champion devices reach a power conversion efficiency (-) of 16.7% and a highest VOC value of 1.45 V, which represents 90% of the DB limit for single-junction PSCs at a bandgap of 1.89 eV. In order to disentangle the nonradiative recombination loss mechanisms, we quantify the origin of energy losses by calculating the radiative limit of the open-circuit voltage (VOCrad) and the quasi-Fermi level splitting (QFLS) of perovskite films with and without other functional layers. We further analyze the strategies to reduce the residual losses in order to push the efficiency beyond the 90% theoretical limit.
CRIS-Team Scopus Importer:2022-11-18